KEANEKARAGAMAN GASTROPODA DI EKOSISTEM MANGROVE PANTAI NEGERI PASSO KECAMATAN BAGUALA KOTA AMBON - Hulopi, Mahriyana; de Queljoe, Kiky M; Uneputty, Prulley A (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2022)
Mangrove ecosystem conditions located on the coast of Passo village can be threatened by land conversion into residential areas. It will ecologically affect the habitat of fauna that is associated in mangrove areas, one of which is gastropod. This study aims to analyze the diversity of the gastropod on the coast of Passo village baguala subdistrics. This research was conducted on November 2020. Gastropod sampling was carried out at five stations using the lineer quadratic transect method. This research shows that sixteen gastropod species have been identified. Terebralia sulcata has the highest values of density, relative abundance and relativefrequency. The diversity index (H') of gastropod communities on the coast of Passo village ranges from 1.76 to 2.30, which is in medium category. The uniformity index ranges from 0.69 to 0.85 which is in high category. The dominance index range from 0.12 to 0.24 which is in low category. In addition, there are fourteen types of mangrove were found in the research location that dominated by the family of Rhizophoraceae. ABSTRAK Ekosistem mangrove yang terdapat di pesisir pantai Negeri Passo dapat terancam oleh sedimentasi akibat pembangunan lahan atas dan alih fungsi lahan menjadi kawasan pemukiman. Tekanan tersebut secara ekologis akan berpengaruh terhadap habitat fauna yang berasosiasi di kawasan mangrove, salah satunya gastropoda. Penelitian ini bertujuan untuk menganalisis keanekaragaman gastropoda pada ekosistem mangrove pantai Negeri passo Kecamatan Baguala. Penelitian ini dilaksanakan bulan November 2020. Pengambilan data sampel gastropoda dilakukan pada 5 stasiun penelitian dengan menggunakan metode transek linier kuadrat.Enam belas spesies gastropoda berhasil diidentifikasi. Terebralia sulcata merupakan spesies dengan nilai rerata kepadatan, kepadatan relative dan frekuensi kehadiran tertinggi, Indeks keanekaragaman (H') gastropoda berkisar antara 1.76-2,30 berada pada kategori sedang, indeks keseragaman gastropoda berkisar antara 0.69-0.85 berada pada kategori hampir merata/tinggi dan indeks dominansi gastropoda berkisar antara 0.12-0,24 berada pada kategori rendah. Untuk vegetasi mangrove di lokasi penelitian ditemukan 14 spesies mangrove yang didominasi oleh Famili Rhizophoraceae. Kata Kunci: Gastropoda, ekosistem mangrove, indeks, kepadatan, keanekaragaman